Determinant Factors of Auditor’s Ability to Detect Fraud: Auditor Proffesional Scepticism as Moderation - Sulistyawati, Ardiani Ika; ., Yulianti; ., Saifudin; A’yun, Annisa Qurrota; Nugroho, Arief Himmawan Dwi; Dwianto, Agus (Journal of Ecohumanism, 2024)
With the moderating effect of auditor professional distrust in mind, this study attempts to investigate the relationship between three key factors fraud audit training, auditor competence, and auditor experience and the auditor’s capacity to identify fraud. This study utilized data collected from 117 auditors who work in Public Accounting Firms located in the center of Java, Indonesia. This study used the Partial Least Squares (PLS) method to address the research hypothesis. The study’s findings demonstrate that an auditor’s expertise and training in fraud auditing have a direct, beneficial impact on their capacity to spot fraud. Nevertheless, the auditor’s expertise has been demonstrated to have no impact on their capacity to identify fraud. The results of this study also managed to demonstrate how an auditor’s professional skepticism enhances the impact of their expertise, experience, and fraud audit training on their capacity to identify fraud.